SARS-CoV-2 strains and clinical profiles of COVID-19 patients in a Southern Brazil hospital - Fam, Bibiana S. de Oliveira; Cadore, Nathan Araujo; Sbruzzi, Renan; Feira, Marilea Furtado; Giudicelli, Giovanna Câmara; de Almeida, Luiz G. P.; Gerber, Alexandra L.; Guimarães, Ana Paula de C.; Vasconcelos, Ana Tereza Ribeiro; Pereira, Alexandre C.; Pereira, Lygia V.; Hünemeier, Tábita; et al. (Frontiers in Immunology, 2024)
IntroductionThe COVID-19 pandemic had a widespread global impact and presented numerous challenges. The emergence of SARS-CoV-2 variants has changed transmission rates and immune evasion, possibly impacting the severity. This study aims to investigate the impact of variants on clinical outcomes in southern Brazil.MethodsIn total, samples from 277 patients, hospitalized and non-hospitalized, were collected between March 2020 and March 2021, before the vaccine was made widely available to the general population in Brazil. Whole genome sequencing of SARS-CoV-2 was performed and bioinformatics and biostatistics analyses were implemented on molecular and clinical data, respectively.ResultsThe study identified significant demographic and clinical differences. The hospitalized group exhibited a higher proportion of males (51.9%) and an increased prevalence of comorbidities, including hypertension (66.0%), obesity (42.6%), and chronic kidney disease (23.6%). Patients were identified with twelve SARS-CoV-2 strains, predominantly B.1.1.28 and B.1.1.33 in the early 2020 first wave, and P.1 overlapping in the late 2020 and early 2021 second wave of COVID-19. Significant differences in hospitalization rates were found among patients infected with the different SARS-CoV-2 lineages: B.1.1.33 (46.0%), B.1.1.28 (65.9%), and P.1 (97.9%). Severity markers, such as pneumonia (62.5%, p=0.002), acute respiratory distress syndrome (ARDS, 72.9%, p<0.001), and oxygen support >6 L/min O2 (64.6%, p<0.001), were more frequent in patients from the second wave. These findings highlight the impact of different variants on the clinical evolution and prognosis of COVID-19, especially when comparing the first and second waves of the pandemic.ConclusionsThe study underscores the association between SARS-CoV-2 strains and COVID-19 severity by integrating clinical and viral data for public health responses during different pandemic phases, highlighting the importance of adapting pandemic strategies as the pandemic evolves.